Effiziente maßgeschneiderte Wärmebehandlung von Blechhalbzeugen in der Serienfertigung - Kahrimanidis, A.; Lechner, Michael; Wortberg, D.; Merklein, Marion (wt Werkstattstechnik - Online, 2015)
By using aluminium alloys in the automotive industry, the mass of cars can be reduced and their environmental compatibility increased. However, the formability of aluminium alloy is limited in comparison to conventional steel material. Therefore, the Institute of Manufacturing Technology has cooperated with the Daimler AG to develop a new approach for enhancing formability by local heat treatment before the forming operation. The technology is known as Tailor Heat Treated Blanks (THTB). This paper presents the efficient integration of the approach in the press shop with respect to technological restrictions. Also, the suitability of different heat treatment methods in dependency of production quantity and the number of variants will be discussed and a recommendation is derived.
CRIS-Team Scopus Importer:2024-02-29